2023
DOI: 10.3390/ijms24076464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human LAV-BPIFB4 Gene Therapy on the Epigenetic Clock and Health of Aged Mice

Abstract: The homozygous genotype of the Longevity-Associated Variant (LAV) in Bactericidal/Permeability-Increasing Fold-Containing Family B member 4 (BPIFB4) is enriched in long-living individuals of three independent populations and its genetic transfer in C57BL/6J mice showed a delay in frailty progression and improvement of several biomarkers of aging and multiple aspects of health. The C57BL/6J strain is a suitable model for studying therapies aimed at extending healthy aging and longevity due to its relatively sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The absence of a positive control in pre-clinical evaluation (Tables 1 and 2) sometimes limits the assessment of the real benefit of the marine compound alternative compared to the gold standard therapy. Moreover, longitudinal studies in aged mice with an appropriate sample size, a blinded design, and strong functional [185] as well as molecular [186] health outcomes are still lacking. In the end, although various potential mechanisms of action for marinederived compounds have been proposed, there is a need for more in-depth investigation of the underlying molecular mechanisms and pathways involved.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a positive control in pre-clinical evaluation (Tables 1 and 2) sometimes limits the assessment of the real benefit of the marine compound alternative compared to the gold standard therapy. Moreover, longitudinal studies in aged mice with an appropriate sample size, a blinded design, and strong functional [185] as well as molecular [186] health outcomes are still lacking. In the end, although various potential mechanisms of action for marinederived compounds have been proposed, there is a need for more in-depth investigation of the underlying molecular mechanisms and pathways involved.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic clocks founded on DNA methylation profiles have emerged as dependable molecular markers of ageing. Simultaneously, frailty assessment tools provide a comprehensive evaluation of overall health during the ageing process [21]. In the study published in this S.I., Giuliani et al [21] demonstrate that systemic gene transfer of LAV-BPIFB4 within aged C57BL/6J mice corresponded to a significant reduction in the epigenetic clock-based biological age, as evaluated using a three-CpG clock methodology.…”
Section: Modelsmentioning
confidence: 99%
“…Simultaneously, frailty assessment tools provide a comprehensive evaluation of overall health during the ageing process [21]. In the study published in this S.I., Giuliani et al [21] demonstrate that systemic gene transfer of LAV-BPIFB4 within aged C57BL/6J mice corresponded to a significant reduction in the epigenetic clock-based biological age, as evaluated using a three-CpG clock methodology. The authors showed that the gene therapy with LAV-BPIFB4 decelerated the age-related DNA hypomethylation in blood cells of old mice, reducing the epigenetic ticking rate, likely mainly in males.…”
Section: Modelsmentioning
confidence: 99%
“…Likewise, delivery LAV-BPIFB4 in mouse model of human diseases improved revascularisation, reduced endothelial dysfunction, atherosclerosis and myocardial infarction-induced damage [ 6 , 9 11 ]. Moreover, LAV-BPIFB4 exhibits rejuvenating effects on the immune and cardiac systems and vasculature accompanied with a deceleration in the progression of frailty [ 10 , 12 14 ]. The benefits of LAV-BPIFB4 are linked to the potentiation of the proteostasis and ribosome biogenesis, [ 6 , 10 ], and the resolution of inflammation through a mechanism that involves the interaction between SDF-1 and CXCR4, a receptor significantly expressed in the myeloid lineage and in macrophages, which promotes the M2 (antinflammatory) skewing of macrophages [ 9 , 15 ].…”
Section: Introductionmentioning
confidence: 99%